Polyvinyl pyrrolidone modified graphene oxide for improving the mechanical, thermal conductivity and solvent resistance properties of natural rubber. Issue 60 (7th June 2016) - Zhang, Xumin; Wang, Jingyi; Jia, Hongbing; Yin, Biao; Ding, Lifeng; Xu, Zhaodong; Ji, Qingmin
Abstract : Graphene oxide is modified by polyvinyl pyrrolidone and modified graphene oxide can remarkably improve the mechanical properties of natural rubber nanocomposite. Abstract : Polyvinyl pyrrolidone (PVP) was applied to modify graphene oxide (GO) to obtain PVP modified GO (PGO). The PGO/natural rubber (NR) nanocomposites were fabricated by mixing a PGO aqueous dispersion with NR latex, followed by coagulation and vulcanization. The structure of PGO was characterized using atomic force microscopy, solid state 13 C NMR, Fourier transform infrared spectroscopy, Raman spectra and X-ray photoelectron spectroscopy. The interaction between GO and PVP molecules as well as the effects of PGO on the mechanical properties, thermal conductivity and solvent resistance properties of the NR matrix were thoroughly studied. The results revealed that PVP molecules might interact with GO via hydrogen bonds. With the addition of PGO, the tensile strength, tear strength and thermal conductivity as well as solvent resistance of the PGO/NR nanocomposites increased. The PGO/NR nanocomposite with 5 phr (parts per hundred rubber) PGO had an 81%, 159%, 30% increase in tensile strength, tear strength, thermal conductivity and a 46% decrease in solvent uptake, respectively, compared with pristine NR.